2005
DOI: 10.1021/jp0508711
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Nonlinear Optical Figure of Merits for Conjugated TTF−Quinone Molecules

Abstract: We have revealed a substantial enhancement of third-order optical figure of merits by the synthesis of a compact molecule possessing the tetrathiafulvalene (TTF) group with two backside C=O groups. Addition of the saturated methylene chain substantially suppresses the third-order optical figure of merits and even local optical hyperpolarizabilities at lambda = 532 nm. Another TTF-derivative molecule possessing ethylenic and acetylenic chains demonstrates large hyperpolarizabilities; however, generally, the fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…[http://dx.doi.org/10.1063/1.4772476] Nonlinear optical (NLO) materials are widely investigated as promising candidates for a variety of applications such as optical communications, optical storage, optical computing, harmonic light generation, optical power limiting, optical rectifying devices, displays, printers, dynamic holography, frequency mixing, and optical switching [1][2][3] for which large second order and/or third order nonlinear optical responses are a prerequisite. In the search for efficient NLO molecular systems, [4][5][6][7] dithiolene metal complexes have been widely investigated. Due to their interesting electronic properties, they have been used for the preparation of singlecomponent molecular metals 8,9 and molecular conductors and superconductors.…”
mentioning
confidence: 99%
“…[http://dx.doi.org/10.1063/1.4772476] Nonlinear optical (NLO) materials are widely investigated as promising candidates for a variety of applications such as optical communications, optical storage, optical computing, harmonic light generation, optical power limiting, optical rectifying devices, displays, printers, dynamic holography, frequency mixing, and optical switching [1][2][3] for which large second order and/or third order nonlinear optical responses are a prerequisite. In the search for efficient NLO molecular systems, [4][5][6][7] dithiolene metal complexes have been widely investigated. Due to their interesting electronic properties, they have been used for the preparation of singlecomponent molecular metals 8,9 and molecular conductors and superconductors.…”
mentioning
confidence: 99%
“…Due to the Kleinman symmetry, the 27 components of the 3-D matrix can be reduced to 10 components. The complete equation for calculating the total static first order hyperpolarizability magnitude of Gaussian output is given as follows (Clodoaldo et al, 2018 andFuks-Janczarek et al, 2005):…”
Section: Nonlinear Optical Properties (Nlo)mentioning
confidence: 99%
“…Since the value of the polarizabilities α and the hyperpolarizability of Gaussian output are reported in a atomic mass units (a.u. ), the calculated values have been converted into electrostatic units (esu) (Fuks-Janczarek et al, 2005).…”
Section: Nonlinear Optical Properties (Nlo)mentioning
confidence: 99%
“…the stable radical cation TTF +• and dication TTF 2+ ) are very useful and versatile π electron donating units and play therefore a major role in the preparation of molecular materials designed for various applications. They have been, for example, used as electron donor molecules to prepare (super)conducting crystalline materials [2][3][4][5], as redox switches in molecular and supramolecular architectures [6][7][8][9][10], as donor components for photovoltaic devices [11][12] as well as donor moieties in nonlinear optical (NLO) materials [13][14][15][16]. For these later materials, numerous studies have shown the important role of both the electron donor and the electron acceptor moieties.…”
Section: Introductionmentioning
confidence: 99%